Food, water, and sanitation insecurities: Complex linkages and implications for achieving WASH security. Issue 11 (2nd November 2022) - Workman, Cassandra L.; Stoler, Justin; Harris, Angela; Ercumen, Ayse; Kearns, Joshua; Mapunda, Kenneth M.
ABSTRACT: Food, water and sanitation insecurities are complex, multi-dimensional phenomena that entail more than availability and access; food, water, and sanitation resources must be safe and culturally appropriate. Researchers and implementers concerned with these insecurities have demonstrated that there are notable interactions between them resulting in significant psychological and biological outcomes. Recent randomised controlled trials (RCTs) in Bangladesh, Kenya (WASH Benefits) and Zimbabwe (SHINE) demonstrated no effect from water, sanitation and hygiene (WASH) interventions on linear growth, and mixed evidence on enteropathogen burden and risk of diarrhoea in young children. These data suggest a need for a more comprehensive understanding of WASH security. The risks posed by multiple resource insecurities shift depending on the individual, their movement throughout their day, their economically and socially prescribed roles, and ecological features such as seasonality and precipitation. By more fully integrating food, water and sanitation security in interventions and subsequent impact evaluations, we can achieve WASH security—one that addresses myriad transmission pathways and co-occurring diseases—that ultimately would improve health outcomes throughout the world. In this critical review, we outline the complexity of combined resource insecurities as a step towards transformative WASH.